"Bipartisanship" as a Detriment to Anti‐Poverty Efforts: Some Contrarian Comments. Issue 3 (18th September 2013) - Skidmore, Max J.
<x xml:space="preserve">Abstract</x> The preoccupation of media and Beltway insiders with "bipartisanship" to the exclusion of policy content is an obstacle to the adoption of effective anti‐poverty measures.